Pengaruh Citra Merek,Kualitas Produk, Dan Harga Terhadap Keputusan Pembelian Produk Kosmetik Focallure Berdasarkan Review Influencer Tasya Farasya (Studi Pada Wanita Yang Melakukan Pembelian Di Online Shop Shopee) - Kristina Firdha Kyswantoro; Rois Arifin; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2021)
ABSTRACTThis study aims to analyze the effect of Brand Image, Product Quality, Price on purchasing decisions for focallure cosmetic products based on the review of influencer Tasya Farasya (a study of women who make purchases at online shopee) either simultaneously or partially. The population in this study were women who made purchases at online shopee. The samples taken were 90 respondents. The sampling technique used was purposive sampling technique. The data were analyzed using multiple linear regression analysis. The results of this study indicate that Brand Image and Product Quality do not have a partial significant effect on purchasing decisions. Price has a partially significant effect on purchasing decisions. And, Brand Image, Product Quality, Price simultaneously influence purchasing decisions. Keywords: Brand Image, Product Quality, Price and purchase decision.